Immigrants Mental Health Issues - Khan, Ahmad; Tidman, Melanie (Jour Med Resh and Health Sci, 2023)
People from different parts of the world migrate to other countries for various reasons, such as warfare, employment, reuniting families, violence, conflicts, and other reasons